2016
DOI: 10.4103/1947-489x.210223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socializing, Fasting and Feasting on Day to Day Blood Glucose Profiles in Diabetes Elucidated by the FreeStyle® Libre™ System

Abstract: Background: Total day-time fasting is observed by millions of adult Muslims during the whole lunar month of Ramadan. However, many people, particularly elderly men and women, do fast isolated or somehow consistent days outside Ramadan. This may pose clinical management challenges. Case Report: A case of an elderly diabetic man observing day-time Ramadan-type fasting on Mondays and Thursdays throughout the year is described. Detailed blood glucose (BG) profiles over a 10 week perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Only few studies reviewed glucose level fluctuation using CGM. [16][17][18][19][20][21] The use of CGM in our population uncovered the incidence of unrecognized hypoglycemia during fasting in adolescents with T1DM. [16] Al-Agha et al reported on the use of FGM system in children and adolescents with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies reviewed glucose level fluctuation using CGM. [16][17][18][19][20][21] The use of CGM in our population uncovered the incidence of unrecognized hypoglycemia during fasting in adolescents with T1DM. [16] Al-Agha et al reported on the use of FGM system in children and adolescents with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…With these features, its place in clinical practice is getting more established in guidance by professional groups and experts (9)(10)(11).A positive impact on glycemic control associated with their usage in both type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) has been reported (12) and their use seems to be expanding in emerging markets (13). Impact of socializing, fasting and feasting outside the month of Ramadan was recently demonstrated in a detailed report in this journal albeit on a single case (14).We are not aware of the use of AGP during the month of Ramadan itself. This is the first report using FGM and AGP to illustrate the changes in blood glucose levels during the month of Ramadan.…”
Section: Introductionmentioning
confidence: 77%
“…In addition to its novelty, this real world experience, albeit involving only a small number of subjects, comprehensively illustrated details captured on all aspects of glucose homeostasis make it particularly valuable. Since this use of this technology is expanding very rapidly, we should miss no any opportunities of learning about its advantages and limitations in the real world (12)(13)(14). A recent study from Germany highlighted how physicians valued the visual presentation of the glucose homeostasis data as AGP and set an example of similar studies in other regions (23).…”
Section: -C 6-c 7-cmentioning
confidence: 99%
See 1 more Smart Citation